Pengaruh Penyuluhan Menggunakan Booklet Terhadap Sikap Wanita Usia Subur (WUS) Untuk Melakukan Pemeriksaan Inspeksi Visual Asam Asetat (IVA) di Kelurahan Duringkang Wilayah Kerja Puskesmas Sei Pancur, Kota Batam - Adhyatma, Aminah Aatinaa; Amir, Eka Fitri; Lisi, Hafizah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Various efforts and global strategies have been carried out by the World Health Organization (WHO) to reduce the incidence and deaths caused by cervical cancer, including through increasing access to information and HPV immunization, as well as prevention efforts such as early screening for cervical cancer. Health promotion is primary prevention that can be done to prevent cervical cancer, various methods can be used in health promotion, one of which is counseling using booklet media which is considered to have many advantages and is effectively used as a companion media for health education.This study aims to determine the effect of counseling using booklets on the attitude of Women of Reproductive Age (WUS) to carry out IVA examinations.This research is a quantitative research with a Quasi Experimental research design. Respondents in this study amounted to 40 people who were divided into 2 research groups, namely the experimental group and the control group. The statistical test used is Wilcoxon sign rank test and the Mann-Whitney test.The results of the research from the Wilcoxon test showed that there were differences in the pre-test and post-test attitudes of WUS in the experimental group and the control group (p<0.05). The results of the Mann-Whitney test showed that there was a significant influence on WUS attitudes between counseling using booklets and conventional counseling (p<0.05). In conclusion, this study shows that booklets are one of the most effective health education media used to influence changes in the attitude of WUS so they want to carry out VIA examinations. This media can be used as a choice of companion media that can be used in health promotion.